ECONOMIC VALUATION OF MANGROVE RESOURCE IN BAROS COAST TIRTOHARGO VILLAGE SUB-DISTRICT OF KRETEK - Djumanto, Tyas Ismi Tria lfhianty Suadi (Sekolah Pascasarjana UGM, 2014)
The community project to plan mangrove in downstream of Opak-OyaRiver has attracted the growingof various socio-economic activities. The objective of the research is to calculate the total economicvalues of mangrove ecosystem. The study was conducted in BarosBantul Regency on September toOctober 2013. The numbers of 41 farmers, 10 fishers, 9 cattlemans and 34 tourists were interviewed tofind out the economic values of mangrove ecosystem. The study indicated the total economic benefits ofmangrove area was IDR168.744.141,67/ha/year, which consist of IDR19.756.491,67/ha/year for directbenefits, IDR132.017.160,00/ha/year for indirect benefits, IDR170.490,00/ha/year for optional benefitsand IDR16.800.000,00/ha/year for existence benefits. The indirect economic benefit of mangrove areawas higher. It shows that ecological functions of mangrove played a greater benefits and the action toconserve and expand the mangrove area are extremely needed. The sustainability of the mangrove andmanagement based on ecology might remain as appropriate way to do in the futur